An architecture of support - Investigating ways small insertions within the informal act as catalysts that support the existing practices and networks established by the residents of Imizamo Yethu - Halfpenny, Macarron (Faculty of Engineering and the Built Environment, 2023)
Informal ways of living have become the new norm in response to our rapidly urbanising world. The logic used in the making of self-built cities is poorly understood and therefore poorly supported. Many of the communities that live in these self-built cities face extreme hardship by having inadequate access to basic services, public space and educational support. As architects, our influence in the built environment is powerful and therefore these issues need to be challenged by using our skills to better the lives of the collective people. The architectural inquiry looks into how the theoretical ideas of informality can be implemented into a design which attempts to weave collaborative responses within an existing self-built environment. This metaphoric idea of weaving is used to guide my studies and test ideas through the design response research. The process of design is used to describe and analyse how the existing environment can be supported in ways which encourage positive change. This dissertation examines the need for sustainable and productive space for the youth of Imizamo Yethu as well as adequate service provision for the community at large. The project seeks to investigate ways small insertions within the existing environment of Imizamo Yethu act as catalysts that support the existing practices and networks established by its residents. The design proposes an architecture which offers support in terms of expression , play and learning as well as access to adequate service provision